Pleiotrophin promotes chemoresistance to doxorubicin in osteosarcoma by upregulating P-glycoprotein - Wu, Dapeng (Oncotarget, 2017)
Chemoresistance is a major hindrance to successful treatment of osteosarcoma (OS). Pleiotrophin (PTN), a neurotrophic growth factor, has been linked to the malignant characteristics of various cancer types. We retrospectively examined the correlation between PTN expression and chemoresistance in OS in a cohort of 133 OS patients. Immunohistochemistry revealed that PTN expression correlated with the necrosis rate and local OS recurrence. In a prognostic analysis, high PTN expression was associated with poor overall and disease-free survival, and was an independent adverse prognostic factor for disease-free survival. In doxorubicin-treated OS cells, PTN knockdown enhanced cellular chemosensitivity, increased the apoptosis rate and inhibited clone formation, while PTN overexpression had the opposite effects. In a xenograft model, PTN knockdown and overexpression respectively enhanced and reduced cellular sensitivity to doxorubicin. PTN upregulated anaplastic lymphoma kinase (ALK), p-Glycogen Synthase Kinase (GSK)3β, β-catenin and multidrug resistance protein 1/P-glycoprotein (MDR1/P-gp). In rescue assays with the β-catenin inhibitor XAV939 and the MDR1/P-gp inhibitor verapamil, PTN promoted chemoresistance to doxorubicin in OS cells by activating ALK/GSK3β/β-catenin signaling, thereby upregulating MDR1/P-gp. Therefore, PTN could be used as a biomarker predicting chemotherapeutic responses, and downregulating PTN could be a promising therapeutic strategy to prevent chemoresistance in OS patients.